2005
DOI: 10.1007/s00415-005-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cognitive impairment

Abstract: The relative frequency of different diagnoses among diabetic and non-diabetic patients attending a memory clinic was similar, indicating that diabetes does not predispose to one particular subtype of dementia. The imaging findings support the notion that the increased risk of cognitive decline and dementia in elderly subjects with diabetes is due to dual pathology, involving both cerebrovascular disease and cortical atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Metabolic syndrome is a risk factor for neurological disorders including stroke, dementia, and depression (Baker et al, 2010; Biessels et al, 2006; Correia et al, 2011; de la Monte, 2009; Haan, 2006; Neumann et al, 2008; Profenno et al, 2010; Zhao and Townsend, 2009). Several studies have demonstrated that factors associated with metabolic syndrome have a negative impact on cognitive health (Dahl and Hassing, 2013; Farr et al, 2008; Luchsinger et al, 2007; Novak and Hajjar, 2010; Takahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome is a risk factor for neurological disorders including stroke, dementia, and depression (Baker et al, 2010; Biessels et al, 2006; Correia et al, 2011; de la Monte, 2009; Haan, 2006; Neumann et al, 2008; Profenno et al, 2010; Zhao and Townsend, 2009). Several studies have demonstrated that factors associated with metabolic syndrome have a negative impact on cognitive health (Dahl and Hassing, 2013; Farr et al, 2008; Luchsinger et al, 2007; Novak and Hajjar, 2010; Takahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using such brain phenotypes, many studies have investigated factors of morphological brain aging such as sex (Coffey et al, 1998; Resnick et al, 2003; Lemaître et al, 2005b; Abe et al, 2010; Hua et al, 2010; O'Dwyer et al, 2012; Ryan et al, 2014), genetics (Lemaître et al, 2005a; Crivello et al, 2010; Boada et al, 2012; Stein et al, 2012; Ryan et al, 2014) or lifestyle (Coffey et al, 1999; Sabia et al, 2014; Shpanskaya et al, 2014; Umene-Nakano et al, 2014). Others have demonstrated the effect on brain atrophy of cardiovascular risk factors such as obesity (Driscoll et al, 2012; Xu et al, 2013; Debette et al, 2014, 2011; Franke et al, 2014), hypertension (Debette et al, 2011; Maillard et al, 2012; Peters, 2012; Beauchet et al, 2013; Franke et al, 2014), hypercholesterolemia (Tendolkar et al, 2012; Van Velsen et al, 2013; Franke et al, 2014), diabetes (Biessels et al, 2005; Debette et al, 2011; Cherbuin et al, 2012; Franke et al, 2014) and tobacco smoking (Enzinger et al, 2005; Ikram et al, 2008; Debette et al, 2011; Durazzo et al, 2012; Hoogendam et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the accelerated cognitive decline observed in DM2, it is also reported that people with DM2 are at greater risk of dementia [2,17]. This risk is most often attributed to the effects of hyperglycaemia on the brain, although severe episodes of hypoglycaemia may also increase its probability [18].…”
Section: Dm2 and Cognitive Impairment: The Mechanismsmentioning
confidence: 99%
“…Despite its apparent detrimental effects, the occurrence of hypoglycaemia in DM2 is not commonly reported, possibly due to patients being unaware of its symptoms when mild hypoglycaemia occurs [15,16]. Further long term investigation of hypoglycaemia's effects on cognitive performance in DM2 is clearly needed.In addition to the accelerated cognitive decline observed in DM2, it is also reported that people with DM2 are at greater risk of dementia [2,17]. This risk is most often attributed to the effects of hyperglycaemia on the brain, although severe episodes of hypoglycaemia may also increase its probability [18].…”
mentioning
confidence: 99%